2007
DOI: 10.1007/s10661-007-9769-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between availability of heavy metals in dry and wetland tailing of an abandoned copper tailing pond

Abstract: Wetland sediments are generally considered as a sink for metals and, in the anoxic zone, may contain very high concentrations of heavy metals in reduced state. A comprehensive study was carried out to compare the differences of total, environmentally available (Env-Av), HOAC, EDTA and DTPA available heavy metal fraction in tailing of the marshy area of a copper tailing pond and the dry tailing. The average concentrations of all the seven metals in the wetland tailing were found higher than dry tailing. Regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Next, soil was ground into powder in ball mill to a finer than 75  μ m sieve size for MTM determination. Physical parameters (pH and EC) were measured according to procedure adopted from Das and Maiti [18], while SOM adopted from Konen et al [19]. Accurately weighed 0.5 g oven dried soil was digested in Teflon beaker with a mixture of acids (HF + HCl) at 130–140°C for complete digestion.…”
Section: Methodsmentioning
confidence: 99%
“…Next, soil was ground into powder in ball mill to a finer than 75  μ m sieve size for MTM determination. Physical parameters (pH and EC) were measured according to procedure adopted from Das and Maiti [18], while SOM adopted from Konen et al [19]. Accurately weighed 0.5 g oven dried soil was digested in Teflon beaker with a mixture of acids (HF + HCl) at 130–140°C for complete digestion.…”
Section: Methodsmentioning
confidence: 99%
“…Das and Maiti [39] reported that EDTA forms water soluble, stable chelated compounds with different metals. EDTA proceeds through a complexing action, solubilizing metals occluded in the carbonates that constitute geochemical matrices.…”
Section: Determination Of Metals In Estuarine Sediments: Comparison Omentioning
confidence: 99%
“…The pH and electrical conductivity (EC) of the collected samples were 4.14 and 0.29 dS m -1 , respectively, with low organic carbon and low available N, P, and K content. The continuous oxidation of pyrite waste was responsible for acidic nature of tailing (Das and Maiti 2008). Along with total concentration of Cu, water extractable and exchangeable forms of Cu were also determined.…”
Section: Chemical Properties Of Tailingmentioning
confidence: 99%